2017
DOI: 10.1097/gme.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Estriol: emerging clinical benefits

Abstract: We conclude transvaginal estriol potentially offers a suitable physiologic delivery and cost-effective alternative to currently available estrogen regimens in selected patients. Additional studies on mode of delivery, safety, and efficacy merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 65 publications
0
18
0
3
Order By: Relevance
“…For instance, while consistent evidence in humans and in the context of pregnancy is lacking, animal and in vitro models show that E2 inhibits the proliferation and cytotoxicity of NK cells [ 68 , 92 ], inhibits Th17 differentiation [ 129 , 130 , 134 , 176 , 186 ], and promotes the differentiation of peripheral Tregs [ 1 , 31 , 72 ]. Some studies have suggested that E3—which exists only during pregnancy—is capable of inhibiting nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB)-mediated transcription, although cell specificity has not been studied [ 4 , 196 ].…”
Section: Maternal Pacemakers Programming the Immune Clock Of Pregnancmentioning
confidence: 99%
“…For instance, while consistent evidence in humans and in the context of pregnancy is lacking, animal and in vitro models show that E2 inhibits the proliferation and cytotoxicity of NK cells [ 68 , 92 ], inhibits Th17 differentiation [ 129 , 130 , 134 , 176 , 186 ], and promotes the differentiation of peripheral Tregs [ 1 , 31 , 72 ]. Some studies have suggested that E3—which exists only during pregnancy—is capable of inhibiting nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB)-mediated transcription, although cell specificity has not been studied [ 4 , 196 ].…”
Section: Maternal Pacemakers Programming the Immune Clock Of Pregnancmentioning
confidence: 99%
“…It is oxidised to oestrone and both oestradiol and oestrone can be converted to oestriol by the liver. Although oestriol bioavailability is higher than oestradiol because of its lower affinity for the sex hormone binding protein [59], oestriol has lower oestrogenic potency than oestradiol (ranging from 1 : 10 to 1 : 100) [60] and greater relative affinity for oestrogen receptor-β than for oestrogen receptor-α, thus minimising extravaginal effects [61]. For this reason, a sequential progesterone for endometrial protection can be omitted [59].…”
Section: Intravaginal Ultralow-concentration Oestriol: Pro and Consmentioning
confidence: 99%
“…It is known that 0.5-1 mg intravaginal oestriol is well absorbed by an atrophic epithelium, and it is equivalent to oral doses of 8-12 mg [63]. Furthermore, oral oestriol administration is associated with entero-hepatic recirculation with prolonged exposure, whereas only 20% of oestriol applied intravaginally reaches the circulation [59]. Intravaginal oestriol improves symptoms of GSM, sexual health, and, more generally, women’s QoL [64].…”
Section: Intravaginal Ultralow-concentration Oestriol: Pro and Consmentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines also promote hematopoietic cell development and function ( 22 ). Nevertheless, estrogen may act on estrogen receptors on EPCs to suppress the expression of genes related to pro-atherosclerosis, whilst promoting the expression of anti-atherosclerosis genes to downregulate proinflammatory cytokine expression ( 23 ).…”
Section: Introductionmentioning
confidence: 99%